Pendeteksian Outlier dan Penentuan Faktor-Faktor yang Mempengaruhi Produksi Gula dan Tetes Tebu dengan Metode Likelihood Displacement Statistic-Lagrange - Makkulau Makkulau; Susanti Linuwih; Purhadi Purhadi; Muhammad Mashuri (Institute of Research and Community Outreach - Petra Christian University, 2010)
There are several problems in industrial process for example problems associated with product quality. In statistics, observation which is significantly different to the average is called outlier. The outlier can give significant influence to the result of modeling, which can affect the decision making. This research develops the outlier detection method using the Likelihood Displacement Statistic method, called Likelihood Displacement Statistic-Lagrange (LDL) method. The LDL method is applied to sugar and molasses production data of Djombang Baru Sugar Factory, Jombang, East Java. The result of this research shows that factors influenced the sugar and molasses production are sugar cane with the dirt less than 5%, sugar cane with the dirt between 5% to 7%, sugar cane with the dirt higher than 7%, and imbibition water